1998
DOI: 10.1002/(sici)1096-9136(199805)15:5<367::aid-dia576>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cryptolepis sanguinolenta: an ethnobotanical approach to drug discovery and the isolation of a potentially useful new antihyperglycaemic agent

Abstract: Evidence has been published that a wide array of plant-derived active principles, representing numerous classes of chemical compounds, demonstrate activity consistent with their possible use in the treatment of patients with Type 2 diabetes mellitus (DM). Despite these interesting observations, to date, metformin is the only ethical drug approved for treatment of Type 2 DM derived from a medicinal plant. Why is this so, given the fact that higher plants are such a potential source of new drugs? The answer to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 4 publications
1
49
0
Order By: Relevance
“…Crude extracts of C. sanguinolenta and their fractions, as well as indoquinoline alkaloids isolated from the plant, have been shown to have activity against Plasmodium falciparum both in vitro and in vivo. [9][10][11][12][13] In addition to studies indicating anti-plasmodial effect, extracts of C. sanguinolenta have been shown to have anti-microbial activity 3,6,[14][15][16][17][18][19][20][21] , to be anti-hyperglycaemic 22,23 and antiinflammatory. 24 A preliminary study of the clinical efficacy of an aqueous extract of C. sanguinolenta as an anti-malarial preparation had been carried out which indicated the efficacy of the extract against falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Crude extracts of C. sanguinolenta and their fractions, as well as indoquinoline alkaloids isolated from the plant, have been shown to have activity against Plasmodium falciparum both in vitro and in vivo. [9][10][11][12][13] In addition to studies indicating anti-plasmodial effect, extracts of C. sanguinolenta have been shown to have anti-microbial activity 3,6,[14][15][16][17][18][19][20][21] , to be anti-hyperglycaemic 22,23 and antiinflammatory. 24 A preliminary study of the clinical efficacy of an aqueous extract of C. sanguinolenta as an anti-malarial preparation had been carried out which indicated the efficacy of the extract against falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%
“…
antihyperglycemic, 8,9) anti-inflammatory 10,11) and antimalarial activities.12-15) Phyto-Riker (Gihoc) Pharmaceuticals Ltd. (Accra, Ghana) has developed an herbal preparation (Phyto-laria ® ) from the dried root of C. sanguinolenta for the treatment of malaria. According to clinical studies, this tea-bag formulation of the root powder (2.5 g) has been shown to be highly effective in the treatment of acute uncomplicated malaria, with an overall cure rate of 93.5%.
…”
mentioning
confidence: 99%
“…The extracts of the roots have been used in folk medicine as an antimalarial agent, in the treatment of rheumatism, and in urinary tract and upper respiratory tract infections for many generations. 2,3) Crude extracts from this plant and their fractions, as well as isolated indoloquinoline alkaloids, have been shown to have antibacterial, [4][5][6][7] antihyperglycemic, 8,9) anti-inflammatory 10,11) and antimalarial activities. [12][13][14][15] Phyto-Riker (Gihoc) Pharmaceuticals Ltd. (Accra, Ghana) has developed an herbal preparation (Phyto-laria ® ) from the dried root of C. sanguinolenta for the treatment of malaria.…”
mentioning
confidence: 99%
“…[22] In a study on Cryptolepis sanguinolenta, alkaloids have been shown to have antihyperglycemic effect in diabetic mouse models, which leads to a decline in blood glucose concentration. [23] A study on Catharanthus roseus (L.) G. Don yielded four alkaloids that were found to be able to ameliorate type 2 diabetes through protein tyrosine phosphatase-1B inhibition. [24] On the other hand, alkaloids isolated from the roots and stems of Berberis L. have antihyperglycemic activity due to its alphaglucosidase inhibition and to decrease glucose transport in the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%